From Informative to Generic: A Systematic Literature Review of Boilerplate KAM (Key Audit Matters) - Nahlia Hanifah; Trianandari Prasetya Nugrahanti (Journal of General Education and Humanities, 2026)
The implementation of ISA 701 on Key Audit Matters (KAM) aims to increase the transparency and communicative value of auditor reports and reduce audit expectation gaps. However, empirical findings suggest that KAM disclosure is increasingly dominated by boilerplate textual practices in the form of redaction uniformity and narrative repetition, which have the potential to degrade the informative value of KAM and make it merely a form of formal compliance. This study aims to systematically synthesize the latest empirical literature to assess the impact of KAM boilerplate on the communicative value of auditor reports and to identify the factors that encourage its occurrence. The research method used is a Systematic Literature Review (SLR) of 18 reputable journal articles indexed in Scopus and published between 2021 and 2025. The results of the synthesis show that the majority of studies found that KAM boilerplate practices significantly lower communicative value, weaken market reactions, and risk creating pseudo-transparency. However, some studies have shown that KAM remains informative when auditors face high audit and litigation risk and actively apply professional judgment. The determinants of KAM boilerplate were identified at five main levels: auditor characteristics, the routine and organizational structure of KAP, client characteristics, the regulatory and institutional context, and linguistic factors. This study concludes that the main problem with KAM lies in implementation practices rather than the design of the ISA 701 standard.